Photo-induced thiol–ene reactions for late-stage functionalization of unsaturated polyether macrocycles: regio and diastereoselective access to macrocyclic dithiol derivatives. Issue 2 (6th December 2019) - Brun, Elodie; Zhang, Ke-Feng; Guénée, Laure; Lacour, Jérôme
Abstract : Stereoselective double hydrothiolation of bis enol ether macrocycles was achieved under photo-mediated conditions. Abstract : Double hydrothiolation of bis enol ether macrocycles was achieved under photo-mediated conditions. The thiol–ene reactions afford a fully regioselective anti-Markovnikov post-functionalization. Thanks to the use of ethanedithiol as reagent, moderate to excellent diastereoselectivity was accomplished leading to macrocycles containing four defined stereocenters in only three steps from 1, 4-dioxane, tetrahydrofuran (THF) or tetrahydropyran (THP).